2015
DOI: 10.5897/ajar2015.9483
|View full text |Cite
|
Sign up to set email alerts
|

Dairy cow welfare assessment on Algerian farms

Abstract: This study is the first to use the Welfare Quality Assessment Protocol (WQ® AP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…According to Bastien et al (2006), the state of dirt of bovine leathers is the highest in winter (around January-February) with proportions of dirty animals reaching the rate of more than one out of five bovines under breeding conditions in France. This latter constant was also observed in Benatallah et al (2015) studies, who reported a high frequency of udder dirt (62.6%), hindquarters (60.6%) and hind limbs (60.6%). Indeed, the increase in the frequency of dirt in animals would be influenced by the nature of the soil, the fecal consistency, the drainage system, the frequency of cleaning as well as the dominance of the housing system hampered (53% of Algerian farms are in zero pasture).…”
Section: Cleanlinesssupporting
confidence: 77%
See 3 more Smart Citations
“…According to Bastien et al (2006), the state of dirt of bovine leathers is the highest in winter (around January-February) with proportions of dirty animals reaching the rate of more than one out of five bovines under breeding conditions in France. This latter constant was also observed in Benatallah et al (2015) studies, who reported a high frequency of udder dirt (62.6%), hindquarters (60.6%) and hind limbs (60.6%). Indeed, the increase in the frequency of dirt in animals would be influenced by the nature of the soil, the fecal consistency, the drainage system, the frequency of cleaning as well as the dominance of the housing system hampered (53% of Algerian farms are in zero pasture).…”
Section: Cleanlinesssupporting
confidence: 77%
“…These results are consistent with De Vries et al (2011) which assessed the influence of body condition on milk production and find that the lower the BCS, the higher the milk yield. Moreover, Benatallah et al (2015) reported that out of the 95 Algerian dairy farms surveyed, 81 farms contained very lean cows (BCS< 2) with an average prevalence of 33.1% ranging from 5.8% to 51.9%.…”
Section: Bcs (Body Condition Score)mentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the results revealed that dairy cows have free access to water in 68.02% of farms; whereas, 31.97% Feeding Practices of Dairy Owners in Semi-arid Region of Algeria of the farms, dairy cows had limited access and water was distributed once a day in winter and twice a day in other seasons. Benatallah et al (2015) showed that the water supply was insufficient in almost all the farms surveyed where the "Long absence of thirst" scores are the lowest. Bourdon et al (2013) recommended making sure that the herds always have the quantity and quality of water needed because a slight under-watering causes an immediate decrease in food consumption and milk production.…”
Section: Livestock Wateringmentioning
confidence: 99%